PENENTUAN UMUR SIMPAN FISH SNACK (PRODUK EKSTRUSI) MENGGUNAKAN METODE AKSELERASI DENGAN PENDEKATAN KADAR AIR KRITIS DAN METODE KONVENSIONAL - AGOES M. JACOEB; MALA NURILMALA; NICOLAS HUTASOIT (Akuatik: Jurnal Sumberdaya Perairan, 2010)
Fish represent one of protein source. Patin ( Pangasius Sp) is representing one of prospect commodity because it has been cultured better. Fish snack (product extrusion) is food which it enhanced with fish to increase its nutrition. Water rate become critical point and determine characteristic of snack during production and depository. Assessment of age keep fish snack was done by acceleration method pursuant to rate of critical water with sorption curve approach. This research aim to evaluate age keep fish snack with critical water rate approach that is isothermal sorption approach curve and compare it with age keep determined by manual calculation. measure This research is divided become 2 phase; especial research and antecedent research. Antecedent research was conducted in a few phase which are making of fish snack, measuring of rout snack parameter through consumer survey, and determinating of characteristic early product using proximate analysis and cracking test. Especial research are conventional method for rate proximate analyze, TPC, TBA, cracking, and organoleptic every week during depository temperature 30 0C. Calculating of critical water rate, balance water rate, model and isothermal sorption curve, MRD value, slope, package permeability, weight and wide package for calculation of age keep Labuza at acceleration method using critical water rate approach. Based on this research; equation model chosen is model Caurie. Critical water rate both types of the product by hedonic; fish snack without flavor is 0,125 g H2O/G solid and fish snack with flavor is 0,078 g H2O/G solid. Based on critical water rate, both types of the product; fish snack without flavor is 0,124 g H2O/G solid and fish snack with flavor is 0,077 g H2O/G solid. Cracking value that obtained on hedonic test 1164,74 gf for snack TF and 874,54 gf for snack DF. Based on rating test, value of cracking is 1164,04 gf for snack TF and 861,38 gf for snack DF. Value of aw for snack TF is 0,15 and 0,16 for snack DF. Age keep fish snack through isothermal sorption curve approach is 2,9-4,3 month for snack TF and 0,4-0,9 month for snack DF by rating test and also hedonic test on RH depository condition about 85 %. At conventional depository method, fish snack have shown of quality retreating of depository for four weeks, but still be consumed. Isothermal sorption curve approach is representing more precise method in determination of age keep fish snack though has not perfect sigmoid curve, according to Labuza statement. Influenced factors of age keep in general are early water rate, critical water rate, balancing water rate, RH, and packaging. Based on this research can be proved that that isothermal sorption curve approach has advantages; easy to be done, effective, efficient, and cheaper than conventional method in determination of age keep fish snack (product extrusion)